1977
DOI: 10.1139/v77-283
|View full text |Cite
|
Sign up to set email alerts
|

Optical study of electrons and positive ions in pulse-irradiated liquid 3-methyloctane at low temperatures

Abstract: HUGH A. GILLIS, NOR MA^ V. KLASSEN, and ROBERT J. WOODS. Can. J. Chem. 55,2022Chem. 55, (1977. The spectrum of pulse-irradiated liquid 3-methyloctane at 127 K has maxima around 625 and 2100 nm. The latter is well-known as being due to the solvated electron (e,-). The former is attrib~~ted to a positive ion because it is eliminated by the addition of triethylamine, but remains in solutions of electron scavengers, and is very similar to bands observed earlier by Louwrier and Hamill in glassy solutions at 77 K o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1979
1979
1989
1989

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…3-Methyloctane. 3MO is probably the hardest of the glasses studied here with a viscosity of 1031 P at 77 K.10 It was of particular interest because of a previous report of a positive ion (RH+), with a Xmax of 625 nm, in liquid 3MO at 127 K. 6 From Figure 1 it can be seen that the positive ion is a more prominent feature in the glassy matrix than in the liquid. We find Xmax ~2000 nm for ef at both 6 and 77 K. The ratio Gemax>6K/GemaXi77K = 0.93 at 2000 nm and ~1.0 at 625 nm.…”
Section: Resultsmentioning
confidence: 77%
See 3 more Smart Citations
“…3-Methyloctane. 3MO is probably the hardest of the glasses studied here with a viscosity of 1031 P at 77 K.10 It was of particular interest because of a previous report of a positive ion (RH+), with a Xmax of 625 nm, in liquid 3MO at 127 K. 6 From Figure 1 it can be seen that the positive ion is a more prominent feature in the glassy matrix than in the liquid. We find Xmax ~2000 nm for ef at both 6 and 77 K. The ratio Gemax>6K/GemaXi77K = 0.93 at 2000 nm and ~1.0 at 625 nm.…”
Section: Resultsmentioning
confidence: 77%
“…A value of Ge(SCN)2' = 2.2 X 104 molecules (100 eV)'1 M'1 cm'1 at 475 nm was used. Corrections were applied for the difference between the electron densities of the hydrocarbon glasses at 77 K and the dosimeter solution but it was assumed that the hydrocarbon densities at 6 a Ge values taken at the spectral maximum, 100 ns after the start of a 40-ns pulse. b Data taken from Kimura, Bremer, and Willard.1 c Comparisons of Ge73K to Ge77K were made at 1800 nm and assumed to be the same at the spectral maximum.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to CCl;' and [CCl: ... C1-] this absorption is quenched by osygen and, therefore, it is concluded that it is a radical species. A comparison of the spectrum with results obtained in acidic sodium chloride solution 1211 shows that the transient might be the Cl; produced according to reaction (7).…”
mentioning
confidence: 83%